Treatment of severe localized pulmonary interstitial emphysema by selective bronchial intubation. Issue 699 (January 1984) - Oliver, J. E.; Smith, I. J.
Abstract : A pre-term infant being ventilated for respiratory distress syndrome developed severe localized pulmonary interstitial emphysema which was successfully treated by selective bronchial intubation.